ANALISIS STRATEGI PT KINOCARE ERA KOSMETINDO - , Suriadi Sumadiwangsa; , Dr. Wakhid Slamet Ciptono, MBA., MPM., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fast Moving Customer Goods (FMCG) industry is a rapidly growing field. FMCG often defined as products that can be sold quickly at a low price. FMCG products in the form of requirements needed on a regular basis, both the food and non-food. From the buyer's perspective, FMCG products can be identified as a product with low price and relatively high purchase frequency. Meanwhile, from the perspective of manufacturers, FMCG products are products that are produced in large volumes and has low margins. With the rapid development of FMCG, business to invite many people to invest. In addition to players, a lot of local entrepreneurs engaged in this business. One of the businesses that see opportunities are PT Kinocare. PT Kinocare is a newcomer in the consumer goods industry in the country. Officially, PT Kinocare began operation in 1991. PT Kinocare run 5 key concept in the People running strategy, Mapping, Cluster, Focus, Drive. If the company does not launch properly and the distribution strategy quickly, consumers will easily switch to competitor products The purpose of this study was to analyze PT Kinocare Era Kosmetindo strategies, data in this study were analyzed qualitatively, of the data collected, either a primary data - obtained through interviews and secondary data - company documents, such as history and the company's organizational chart. Analysis using SWOT and five forces analysis in order to get conclusions on the strategy and the constraints faced. Based on the analysis, we concluded that the strategy pursued by the Mapping, Cluster, Focus, Drive PT Kinocare Era Kosmetindo has made the right decision. By implementing this strategy the company can achieve its goal to develop innovative products. Through external analysis can be seen that the driving forces of the consumer goods industry are: government deregulation, changes in lifestyle / lifestyle, and growth industri.Kunci PT Kinocare Era Kosmetindo success lies in innovation strategy and continue menggembangkan innovative products.